2009
DOI: 10.1021/ol9017479
|View full text |Cite
|
Sign up to set email alerts
|

Direct Enantioselective Organocatalytic Hydroxymethylation of Aldehydes Catalyzed by α,α-Diphenylprolinol Trimethylsilyl Ether

Abstract: The direct enantioselective hydroxymethylation of aldehydes utilizing alpha,alpha-diphenylprolinol trimethylsilyl ether as an organocatalyst is described. The intermediate alpha-substituted beta-hydroxyaldehydes were not isolated but converted to the more readily isolable derivatives. For example, the derived hydroxy acids were isolated in up to 94% yield with excellent enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 29 publications
1
43
0
1
Order By: Relevance
“…33,34 The hydroxymethyl group was introduced via an aldol condensation with formaldehyde that was ultimately trapped as the silyl ether of the formacetal ( 11 ) using a chiral catalyst derived from proline. 35 Substituting Selectfluor ® for N -bromosuccinimide, which was used in the synthesis of the DOB precursor, to induce cyclization of 11 by oxidatively cleaving the 1,3-dithiane resulted in a significant improvement in yield, albeit as an inseparable mixture of diastereomers of 12 . 36 Two of the 4 diastereomers were separable upon desilylation to 4 .…”
Section: Resultsmentioning
confidence: 99%
“…33,34 The hydroxymethyl group was introduced via an aldol condensation with formaldehyde that was ultimately trapped as the silyl ether of the formacetal ( 11 ) using a chiral catalyst derived from proline. 35 Substituting Selectfluor ® for N -bromosuccinimide, which was used in the synthesis of the DOB precursor, to induce cyclization of 11 by oxidatively cleaving the 1,3-dithiane resulted in a significant improvement in yield, albeit as an inseparable mixture of diastereomers of 12 . 36 Two of the 4 diastereomers were separable upon desilylation to 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Worse results were achieved when aldehydes 55 bearing aromatic rings, oxygen, or other functionalities at the α-position were used in the hydromethylation process. This methodology was used as a key step for the synthesis of (−)-rasfonin [347].…”
Section: Aldehydes As Source Of Nucleophilementioning
confidence: 99%
“…Though styrenyl-based substrates are known to have a preference for the branched regioisomer,11 α-substituted styrenes have been reported to be highly linear-selective 12. During the course of our studies we found that the branched aldehyde product is unstable to silica gel purification, and also dimerizes to a small extent to a cyclic acetal 13. To circumvent these problems we oxidize the unpurified reaction mixture directly and isolate the carboxylic acid product.…”
mentioning
confidence: 97%